สุนทรียภาพในกลอนลำของหมอลำกลอน : องค์ประกอบและปัจจัยเกื้อหนุนต่อการสร้างสรรค์ - บงสิทธิพร ราตรี ศรีวิไล; ชนไพโรจน์ เจริญชัย; สมจิตศรีปัญญา สุภณ (Journal of Fine and Applied Arts Khon Kaen University, 2014)
กลอนลำเป็นองค์ประกอบที่สำคัญยิ่งในการสร้างชื่อเสียงให้แก่หมอลำ ถ้ากลอนลำดีก็ทำให้ผู้ฟังประทับใจ กลอนลำจะดีมีสุนทรียภาพก็ขึ้นกับประสบการณ์ และทักษะความรู้ความชำนาญของผู้แต่งกลอน การวิจัยนี้เป็นการวิจัยเชิงคุณภาพ มีความมุ่งหมายเพื่อ 1. เพื่อศึกษาถึงองค์ประกอบทางสุนทรียภาพในกลอนลำของหมอลำกลอน และ 2. เพื่อศึกษาปัจจัยที่เกื้อหนุนต่อการสร้างสรรค์กลอนลำที่มีสุนทรียภาพ มีการเก็บข้อมูลทั้งข้อมูลเอกสารและข้อมูลภาคสนาม เครื่องมือที่ใช้ในการวิจัยได้แก่ แบบสัมภาษณ์ แบบสังเกต และแบบสนทนากลุ่ม มีการเก็บข้อมูลภาคสนาม ตั้งแต่เดือนตุลาคม 2552 ถึง เดือนตุลาคม 2553 โดยการสัมภาษณ์ การสังเกต และการสนทนากลุ่ม ข้อมูลภาคสนาม ได้จากการ สัมภาษณ์ การสังเกต และ การสนทนากลุ่ม จากผู้รู้ 5 คน ผู้ปฏิบัติ 15 คน ผู้ให้ข้อมูลทั่วไป 10 คน ในเขตพื้นที่จังหวัดหนองคาย อุดรธานี ขอนแก่น มหาสารคาม ร้อยเอ็ด อำนาจเจริญ และอุบลราชธานี ผู้ให้ข้อมูลทั้งหมดนี้ประกอบด้วย นักวิชาการ หมอลำ นักแต่งกลอนลำ และผู้จัดรายการวิทยุด้านหมอลำ นำข้อมูลมาตรวจสอบความถูกต้องด้วยวิธีการแบบสามเส้าา วิเคราะห์ตามจุดมุ่งหมายที่ตั้งไว้ และนำเสนอผลการวิจัยใน รูปแบบพรรณนาวิเคราะห์ ผลการวิจัยพบว่าา องค์ประกอบทางสุนทรียภาพในกลอนลำของหมอลำกลอน ด้านเนื้อหาา ซึ่งได้แก่ เรื่อง ความรัก ความเชื่อ คำสอน ความงามของธรรมชาติ วิถีชีวิต และขนบธรรมเนียมประเพณี ด้านรูปแบบหรือฉันทลักษณ์ของกลอนลำ ได้แก่ กลอนร่าย กลอนกาพย์ กลอนเยิ้น และ กลอนเพลง ด้านศิลปะในการใช้ถ้อยคำ ได้แก่ การใช้ถ้อยคำที่สื่อความหมายได้ตรง ชัดเจน กระชับ การใช้คำสัมผัส คำอุปมาอุปมัย คำที่เป็นสุภาษิต คำคม และโวหารที่ก่อให้เกิดความสะเทือนอารมณ์แก่ผู้อ่านหรือผู้ฟัง ปัจจัยที่เกื้อหนุนต่อการสร้างสรรค์กลอนลำที่มีสุนทรียภาพนั้น ผู้แต่งกลอนลำแต่ละคนนั้น จะต้องมีความรู้ดังต่อไปนี้ คือ 1. ความรู้ด้านเนื้อหา 2. ความรู้ด้านรูปแบบและฉันทลักษณ์ และ 3. ความรู้ด้านศิลปะในการใช้ถ้อยคำ ซึ่งความรู้และทักษะทั้ง 3 ด้านนี้ ได้จากการสั่งสมประสบการณ์ต่าง ๆ ที่ผ่านเข้ามาในชีวิตของนักแต่งกลอนลำแต่ละคน ประสบการเหล่านี้ได้แก่ 1. การศึกษาเล่าเรียนทั้งนอกระบบและในระบบโรงเรียน 2. การมีอาชีพศิลปินหมอลำ 3. ประสบการณ์พิเศษในชีวิต 4. การเรียนรู้จากครู 5. การมีประสบการณ์ทางภาษาา วรรณกรรมและขนบธรรมเนียมประเพณีจากการบวชเรียน 6. การศึกษาค้นคว้าด้วยตนเอง 7. การมีใจรักและขยันหมั่นเพียรด้านการแต่งกลอน และ 8. ความรักในการอ่าน การคิด การสังเกต และการใฝ่ฝัน ของนักแต่งกลอนลำ ประสบการณ์ทั้งหลายเหล่านี้ต่างก็มีส่วนช่วย โดยสรุป กลอนลำเป็นองค์ประกอบที่สำคัญยิ่งส่วนหนึ่งที่ช่วยให้หมอลำมีชื่อเสียง เป็นที่นิยมในหมู่ผู้ฟัง การที่ผู้แต่งกลอนลำจะแต่งกลอนให้มีสุนทรียภาพได้นั้น ต้องเป็นผู้มีความรู้และทักษะทั้งสามด้าน คือ ด้านเนื้อหา ด้านรูปแบบและฉันทลักษณ์ และด้านศิลปะในการใช้ถ้อยคำ ด้วยเหตุนี้ จึงสมควรที่จะมีหลักสูตรการประพันธ์วรรณกรรมท้องถิ่น ในทุกระดับการศึกษาา เพื่อส่งเสริมให้เกิดผู้ประพันธ์กลอนลำที่มีความรู้ความสามารถจำนวนมากขึ้น อันจะช่วยส่งเสริมให้หมอลำมีกลอนลำที่มีสุนทรียภาพมาใช้ลำเพื่อความรู้และความบันเทิงแก่ผู้ฟังสืบไป Aesthetics in Lam Klon Texts : Elements and Supportive Factors for Creativities A Klon Lam text is very important factor for enhancing the fame of a molam singer. If a klon lam text is is good, it will impress the audience. A good klon lam text, with aesthetics, depends on the experiences and skills of a klon lam text writer. This qualitative research aimed at : 1) examining the aesthetics elements in klon lam text of molam klon singers; and 2) investigating the supportive factors in klon lam text creation. The research tools consisted of an interview form, an observation form, and a group discussion form Written documents and fieldwork data were gathered. Fieldwork data were collected through interviews, observations, and group discussions through 5 key-informants, 15 casual informants, and 10 general informants in Nong Khai, Udon Thani, Khon Kaen, Maha Sarakham, Roi Et, Amnat Charoen, and Ubon Ratchathani. These informants were academicians, senior molam singers, klon lam text writers, and radio program promoters on lam singing. The data were checked for their accountability with the triangulation technique, analyzed in accordance with the given objectives, and the research results were presented in a descriptive analysis form. The results of the study revealed that the aesthetics elements in a klon lam text of lam klon singing were classified into 3 elements : content, form, and arts of word using. A klon lam contents included love, beliefs, proverbs, the beauty of natural sceneries, and customs; the overall form and internal form of a klon lam text consisted of klon rai, klon kap, klon nyoen, and klon phleng forms; and the arts of word using included : a straight, clear, brief, and the use of rhyming, metaphoric, proverb, incisive, and emotional impressive words that affected the emotion of the readers and the audience. In terms of he supportive factors for the aesthetics klon lam text creativities, it was found that the individual writer had to posses the 3 following aspects of knowledge : 1) content aspect; 2) poetic form aspect; and 3) arts of word using aspect. The 3 aspects of knowledge and skill of each klon lam writer were acquired through the following experiences : school attending, formal and informal; 2) lam singing experiences; 3) extraordinary experience in life; 4) learning from teacher; 5) experiences in languages, literature, and customs in monkhood; 6) self studies; 7) love and diligence in klon lam writing; and 8) the love inreading, thinking, observing, and dreaming. Each of these experiences, knowledge on klon lam content, knowledge on klon lam form, and knowledge on the art of words using, had eventually been formed the 3 necessary supportive factors for the creation of aesthetical klon lam texts. In conclusion, a klon lam text is one of the most important elements that helps a molam becoming popularized among the audience. To become an able klon lam text writer in writing an aesthetical text, one has to posses 3 aspects of knowledge and skills. These include content, literary form, and arts of word using. Therefore, local poetry writing should be established in all school system levels. Then we can build up more able klon lam text writers to create aesthetical klon lam texts for molam singers. Molam singers can use them in their performances to continuously serve the audience in terms of knowledge and entertainment.